2021
DOI: 10.1542/peds.2020-035550
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Imaging in Children With Multicystic Dysplastic Kidney or Solitary Kidney

Abstract: BACKGROUND AND OBJECTIVES Children with isolated unilateral multicystic dysplastic kidney (MCDK) or congenital solitary kidney (CSK) undergo serial renal ultrasonography with variable frequency until they are transitioned to adult care. A growing body of literature suggests the value of frequent ultrasonography in this population is limited, providing no benefit to overall outcomes. Despite emerging evidence, ultrasound remains overused, resulting in avoidable health care expenditures and unn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Recently, Jawa et al showed that he development of a specific algorithm could reduce by 47% the proportion of avoidable ultrasounds ordered in CSFK children resulting in about $46,000 of annual savings [10]. Our cost analysis showed that ERUSA could further reduce the costs when applied to the analyzed follow-up protocols without missing long-term important prognostic information (Table 4).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Recently, Jawa et al showed that he development of a specific algorithm could reduce by 47% the proportion of avoidable ultrasounds ordered in CSFK children resulting in about $46,000 of annual savings [10]. Our cost analysis showed that ERUSA could further reduce the costs when applied to the analyzed follow-up protocols without missing long-term important prognostic information (Table 4).…”
Section: Discussionmentioning
confidence: 70%
“…To identify earlyin-life predictors of absence of KI in adulthood could be useful in personalizing follow-up protocols of CSFK children in order to reduce unnecessary medicalization with impact on stressful procedures (such as blood sample collection in children) and economic costs. We also estimated the cost saving of integrating the current follow-up protocols [2,10] with the early RUS algorithm (ERUSA) (secondary outcome). The ERUSA is based on the hypothesis that early RUS could provide the instruments to personalize follow-up.…”
Section: Of 16mentioning
confidence: 99%
See 3 more Smart Citations